2011
DOI: 10.1177/1471301211421225
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of the validation method: Nurses' descriptions of caring relationships with residents with dementia disease

Abstract: This study describes nurses’ experiences of relationships with residents with dementia disease (1) before and after validation method (VM) training and (2) after extensive experience using the VM. An intervention was performed in a nursing home, involving supervision plus one year of training in using the VM. Nurses were interviewed before and after the intervention. Nurses with extensive VM experience, working at another nursing home, were interviewed once. Qualitative content analysis of the transcribed inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
56
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(63 citation statements)
references
References 23 publications
7
56
0
Order By: Relevance
“…Eight detailed qualitative studies of training-interventions were available (Chenoweth et al, 2015;Figueiredo, Barbosa, Cruz, Marques, & Sousa, 2013;Hammar et al, 2011;Lykkeslet et al, 2014;Soderlund et al, 2013;Soderlund et al, 2016;Soderlund, Cronqvist, Norberg, Ternestedt, & Hansebo, 2016;Soderlund, Norberg, & Hansebo, 2012, 2014. As previously discussed the methodology and focus of these studies was diverse, and the quality was variable.…”
Section: Acceptability: Satisfaction and Qualitative Datamentioning
confidence: 99%
See 1 more Smart Citation
“…Eight detailed qualitative studies of training-interventions were available (Chenoweth et al, 2015;Figueiredo, Barbosa, Cruz, Marques, & Sousa, 2013;Hammar et al, 2011;Lykkeslet et al, 2014;Soderlund et al, 2013;Soderlund et al, 2016;Soderlund, Cronqvist, Norberg, Ternestedt, & Hansebo, 2016;Soderlund, Norberg, & Hansebo, 2012, 2014. As previously discussed the methodology and focus of these studies was diverse, and the quality was variable.…”
Section: Acceptability: Satisfaction and Qualitative Datamentioning
confidence: 99%
“…However, studies offered an insight into some of the benefits of training-interventions; for example, seeing behaviour that challenges as communicating a need of the people living with dementia and working more creatively to reduce aggression or increase wellbeing and cooperation (such as, using music or singing) (Hammar et al, 2011;Lykkeslet et al, 2014). They also provided information regarding how communication could be improved following training interventions; for example, studies on Validation Method indicated that nurses communication could change from being controlling and not attending to the potential meaning of the people living with dementia to being more attentive and following the pace and conversational meaning of people living with dementia (Soderlund et al, 2013;Soderlund et al, 2012). Further the findings of Chenoweth et al (2015) indicate some of the challenges in supporting organisational change and maintaining skills learnt in training; for example, managers supporting staff to continue implementing changes by providing adequate staff education and supervision.…”
Section: Acceptability: Satisfaction and Qualitative Datamentioning
confidence: 99%
“…The study reported in this article was part of an intervention that included a 1‐year implementation of the VM in a training programme on three wards at a nursing home (NH) in a large Swedish city, described in detail elsewhere (Söderlund et al ., ). Before the programme, the entire nursing staff from all three NH wards was invited to a lecture about the VM and the programme.…”
Section: Methodsmentioning
confidence: 97%
“…Studies have shown fewer stress reactions among nurses who used emotion‐oriented care including VM (Finnema et al ., ), and more effective responses to needs and behaviour expressed by residents with dementia than among nurses with no VM training (Fine & Rouse‐Bane, ). However, considering the extensiveness of the training programme required for the VM (Söderlund et al ., ), it seems important to study nurses' experiences of such a programme and to examine whether the programme has any influence on work climate among the entire nursing staff. As far as we know, this has not been studied before.…”
Section: Introductionmentioning
confidence: 97%
“…According to earlier studies, non‐pharmacological treatment should always be considered first (Herrmann & Gauthier, ; Hogan et al ., ; Kvernmo et al ., ). This treatment aims to create a positive environment for persons with dementia, and might include caregivers singing (Hammar Marmstål et al ., ), validation therapy (Neal & Briggs, ; Soderlund et al ., ), and reminiscence therapy (Woods et al ., ).…”
Section: Introductionmentioning
confidence: 99%